Processi inferenziali vs processi di codifica/decodifica nei modelli di trasmissione dellíinformazione fra individui - Bonacci, Fabrizio (Rivista Italiana di Filosofia del Linguaggio, 2009)
According to some cognitive scientists, the informative content of a given utterance seems to be fully encoded within the strings of syntactical elements that constitute any sentence. By contrast, an increasing number of studies, which lay on the borderline between pragmatics and cognitive science, suggest that the inferential processes of comprehension might play a key role into communicative contexts. In this paper I am going to analyze some of the key concepts involved within the communicative interaction among individuals. The problem I would like to handle here is the following. If we are inclined to assume that cognitive systems can be theorized as natural devices that process information, then we should be able to provide an answer to this question: what is the role played by the encoding/decoding processes of information compared with the inferential procedures of comprehension? A bit more broadly, would it be plausible to imagine to integrate the general model of communication, which is based on the encoding/decoding processes of information, with an inferential model of comprehension? The aim of this paper is to suggest a few reasons, both theoretical and empirical, according to which such an integration seems to be quite implausible. Alternatively, I will try to show that an inferential model of communication might be more plausible, both from a theoretical and an empirical point of view.